Association of Insulin and Lipoprotein Level in Subjects of T2dm and Non Diabetics - Sheema Khan, Nasir Rashid, Rukhsana Gulzar, Zahra Batool (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare and correlate the serum insulin and lipoprotein levels in diabetics and non-diabetics. Methods: A cross-sectional study with total of 88 subjects. These were divided into three groups i.e. A, B, C. Group A constitutes 34 cases of newly diagnosed T2DM and group B includes 34 cases on oral hypoglycemic treatment. Group C includes 20 subjects as controls which were age and sex matched. Blood glucose level, HDL-c and LDL-c were done in the lab. By usual methods and insulin level was done by ELISA methods. Results: In diabetic groups i.e. A and B, mean insulin levels were significantly lower and glucose and LDL-c levels were significantly higher than control group i.e. group C. HDL-c level was similar in diabetic groups (A and B) and control group (group C). There was found no correlation between insulin and lipoproteins in this study. Conclusions: Insulin level was higher in control group as compared to study subjects and this difference was not statistically significant. LDL-c level was higher in diabetic group i.e. A and B as compared to control group (C) and this difference was statistically significant. Association between insulin and lipoproteins is non significant statistically. Keywords: Insulin, Lipoprotein, Type-2 diabetes